Medroxyprogesterone acetate positively modulates specific GABAA-receptor subtypes - affecting memory and cognition - Das, Roshni; Ragagnin, Gianna; Sjöstedt, Jessica; Johansson, Maja; Haage, David; Druzin, Michael; Johansson, Staffan; Bäckström, Torbjörn (Psychoneuroendocrinology, 2022)
Medroxyprogesterone acetate (MPA) is a progestin widely used in humans as hormone replacement therapy and at other indications. Many progestin metabolites, as the progesterone metabolite allopregnanolone, have GABAA-receptor modulatory effects and are known to affect memory, learning, appetite, and mood. In women, 4 years chronic treatment with MPA doubles the frequency of dementia and in rats, MPA causes cognitive impairment related to the GABAergic system. Activation of the membrane bound GABAA receptor results in a chloride ion flux that can be studied by whole-cell patch-clamp electrophysiological recordings. The purpose of this study was to clarify the modulatory effects of MPA and specific MPA metabolites, with structures like known GABAA-receptor modulators, on different GABAA-receptor subtypes. An additional aim was to verify the results as steroid effects on GABA response in single cells taken from rat hypothalamus. HEK-293 cell-lines permanently expressing the recombinant human GABAA-receptor subtype α1β2γ2L or α5β3γ2L or α2β3γ2S were created. The MPA metabolites 3α5α-MPA,3β5α-MPA and 3β5β-MPA were synthesised and purified for electrophysiological patch-clamp measurements with a Dynaflow system. The effects of MPA and tetrahydrodeoxycorticosterone were also studied. None of the studied MPA metabolites affected the responses mediated by α1β2γ2L or α5β3γ2L GABAA receptors. Contrary, MPA clearly acted both as a positive modulator and as a direct activator of the α5β3γ2L and α2β3γ2S GABAA receptors. However, in concentrations up to 10 μM, MPA was inactive at the α1β2γ2L GABAA receptor. In the patch-clamp recordings from dissociated cells of the preoptic area in rats, MPA increased the amplitude of responses to GABA. In addition, MPA alone without added GABA, evoked a current response. In conclusion, MPA acts as a positive modulator of specific GABAA receptor subtypes expressed in HEK cells and at native GABA receptors in single cells from the hypothalamic preoptic area. •The study shows that medroxyprogesterone-acetate (MPA) acts like a positive modulator on the alpha 5 and alpha 2 GABA-A receptor but not on the alpha1 subtype of GABA-A receptors. This may explain MPAs enhancement effect on dementia progress in women’s mental health study.•Medroxyprogesterone-acetate (MPA) is a positive modulator on the alpha 5 and alpha 2 GABA-A receptor.•MPA does not modulate the alpha 1 subtype of GABA-A receptor.